PESAN SEMIOTIKA DI BUNGKUS ROKOK DAN PENGARUHNYA PADA PEROKOK AKTIF - Fazri, Anhar; abidin, zainal (Universitas Teuku Umar, 2017)
This article discusses the existing semiotic messages on cigarette packs and the impact on activesmoking, with research taking place in the Village of Alue Tho Seunagan District of Nagan Raya.The goal is to get the extent of the effectiveness or the effect of the semiotic messages and thenumber of public awareness to reduce the level of smoking addiction. in writing this article usingdescriptive quantitative research method is a method that discusses the current state based ondata and research analysis. The data collection technique used observation and questionnairesto the respondent sample collection techniques using random sampling (random selection) is thewhole object of the total population sampled 30 people ie 10% of the total population of 300people, special people active smokers. These results can be seen the impact of the influence ofsemiotics messages through images on every cigarette packaging 60% affected from the entireinformant, and 40% are not affected. The conclusion of the affected would have to consider theeffect or stop smoking, then that is not affected by the effects do not exist. The effect influence theattitudes, behaviors and actions. It signifies the process of delivering the message conveyedproperly. From the results of the most active smokers get the effect will be to change attitudes andviews on smoking.